Developing protean career behavior through employability culture and mentoring: career strategies as moderator - Wong, Siew Chin; Mohd Rasdi, Roziah; Abu Samah, Bahaman (2016)
The purpose of this study was to examine the relationship among organizational related variables and the moderating role of career strategies on protean career among employees. Research data were gathered from a sample of 306 selected employees in 18 Electrical and Electronics multinational corporations (MNCs) in Malaysia. Partial Least Squares Structural Equation Modelling (PLS-SEM) is employed to examine the influences of organizational -related variables (i.e., employability culture and mentoring) and the moderating role of career strategies on a protean career. The results demonstrate that organizational-related variables, namely employability culture and mentoring are viewed as potential predictors of protean career. Career strategies is significantly moderate the relationship between both employability culture and mentoring and protean career among employees. This study provides an empirical framework to explain organizational-related variables in influencing protean career based on the review of career related literatures. The findings provide implications to both organizations and HRD practitioners on new career trends of a protean career. Practical interventions are suggested to assist individuals and organisations towards protean career development. This study offers new insight into the predictors of protean career by exploring organizational-related variables and the moderating role of career strategies on a protean career.